Penerapan Undang Undang Otonomi Daerah No. 32 Tahun 2004 Jo Perda No. 7 Tahun 2006 di Waru Sidoarjo - Azmi M., Ulul (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2013)
Abstract: This article is a field research on the application of the Regional Autonomy Law No. 32 year 2004, jo PERDA (Regional Regulation) No. 7 year 2006 about the local government in Waru-Sidoarjo. The research was conducted by interviewing some people from four villages, namely Ngingas, Kepuh Kiriman, Tambak Oso, and Tambak Rejo. The research concludes that the community of the four villages had been carrying out the mandate of the Regional Autonomy Law No. 32 year 2004, jo PERDA (Regional Regulation) No. 7 year 2006. However, the compliance in carrying out the law is not based on their legal awareness. It is because there are some laws that are considered as discrimination and murder of the rights of individuals, including the prohibition of the village government to take charge of the political party (consulting / comparative study) ". It can, of course, kill the principles of human rights and democracy, whereas the legislation itself gives respect to the principles of democracy and human rights. The principles to be considered in formulating constitution is the guarantee of human rights of each member of society and the equality of all people before the law without any distinctions of social statification.Keywords: Implementation, regional autonomy law, Waru